2019
DOI: 10.1021/acs.jpcc.9b02002
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Assisted Supramolecular Control over Fluorescence Resonance Energy Transfer in Aqueous Medium

Abstract: The supramolecular approach has been exploited to modulate the fluorescence resonance energy transfer between an oligofluorene fluorophore and an ionic styryl dye with the assistance of a protein (bovine serum albumin) in aqueous medium. Self-assembled nanoparticles of oligofluorene with a negatively charged surface have functioned as the energy donor, and the positively charged styryl dye acts as the energy acceptor. The hydrophobic pockets in the secondary structure of the added protein enabled complimentary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Variable temperature (VT) UV/Vis studies of 1 b at pH 3 showed minor spectral changes, that is, weak coupling of the OPE units upon cooling from 363 to 351 K, with negligible shifts of the absorption maximum ( λ max =335 nm; Figure a). Further cooling down to 283 K resulted in a slight increase of absorption with a small redshift in λ max without any clear isosbestic point (Figure a), which is in line with the formation of disorganized aggregates . Moreover, the formation of a weak aggregate shoulder band around 400 nm accompanied by a reduction of absorption around 270 nm are in accordance with the formation of small‐sized aggregates (Figure a).…”
Section: Methodssupporting
confidence: 51%
“…Variable temperature (VT) UV/Vis studies of 1 b at pH 3 showed minor spectral changes, that is, weak coupling of the OPE units upon cooling from 363 to 351 K, with negligible shifts of the absorption maximum ( λ max =335 nm; Figure a). Further cooling down to 283 K resulted in a slight increase of absorption with a small redshift in λ max without any clear isosbestic point (Figure a), which is in line with the formation of disorganized aggregates . Moreover, the formation of a weak aggregate shoulder band around 400 nm accompanied by a reduction of absorption around 270 nm are in accordance with the formation of small‐sized aggregates (Figure a).…”
Section: Methodssupporting
confidence: 51%
“…Since TS-CDs is highly hydrophobic and possesses aggregation-induced emission property, solvent effect, we speculate that TS-CDs can response to HSA and emission enhanced. Researchers had proved that the addition of HSA can reduces the polarity of the system and will inhibit the rotation or vibration of the fluorophore (Chakrabarty et al, 2007;Vijayakumar et al, 2019;Xu et al, 2016). The fluorescence of TS-CDs increases with the addition of HSA due to the decreased of solvent polarity, which is consistent with the optical properties of TS-CDs that fluorescence intensity increased as the water fraction decreased from 90% to 60%.…”
Section: Detection Of Hsamentioning
confidence: 57%
“…To mimic the delicate biological functions involving natural helices and decipher the transition process of hierarchical architectures, recently, effort has been devoted to explore the functionalized and morphological processes via developing the straightforward approaches toward reconstructive natural helical systems. 3 For instance, α-helices in proteins have been well modified and successfully used as building blocks in the controllable construction of hierarchical superstructures, such as micelles, vesicles, hydrogels, and organic–inorganic hybrids, 4 which have been further applied for controlled release, biological simulation, and tissue engineering. 5 However, it is still an important challenge in the case of synthetic helical systems because of their elusive assembly mechanism based on the complex multiple driving forces between helices.…”
Section: Introductionmentioning
confidence: 99%